A systematic review of the parenting and outcomes experienced by offspring of mothers with borderline personality pathology: Potential mechanisms and clinical implications. (July 2016) - Eyden, Julie; Winsper, Catherine; Wolke, Dieter; Broome, Matthew R.; MacCallum, Fiona
Abstract: There is growing interest in whether the parenting strategies and offspring outcomes of mothers with borderline personality disorder (BPD) differ from those of mothers without BPD. We searched PsychINFO, PubMed, EMBASE, Web of Science, Scopus and ASSIA databases for studies examining parenting skills and attitudes among mothers with BPD/BPD symptoms and/or offspring outcomes. PRISMA reporting guidelines were followed. Of 10, 067 abstracts screened, 101 full-text articles were retrieved and 33 met pre-determined criteria for qualitative synthesis. Overall, studies suggest that mothers with BPD/BPD symptoms are more likely to engage in maladaptive interactions with their offspring characterised by insensitive, overprotective, and hostile parenting compared to mothers without BPD/BPD symptoms. Adverse offspring outcomes include BPD symptoms, internalising (including depression) and externalising problems, insecure attachment patterns, and emotional dysregulation. Findings suggest that vulnerability from mother to offspring may be partly transmitted via maladaptive parenting and maternal emotional dysfunction. Conclusions were limited by study heterogeneity in methodology and construct definitions, as well as a paucity of clinical comparison groups. Prospective studies of mothers with BPD and their offspring from pregnancy onwards may further elucidate mechanisms of transmission and identify resilience factors across development. Parenting behaviour awareness, improving attachment behaviours and emotional regulation strategies may be important intervention targets. Highlights: We systematically examined maternal borderline personality, parenting and offspring outcomes Studies suggest mothers with borderline personality display maladaptive parenting behaviours Offspring outcomes include insecure attachment and various psychopathology Maladaptive parenting and maternal emotion dysregulation were potential mediators Intervention targets include awareness, emotion regulation and attachment strategies